2009
DOI: 10.1007/s00134-009-1523-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for ventilator-associated pneumonia after major heart surgery

Abstract: VAP is common in patients undergoing MHS that require more than 48 h of MV. In that "high-risk" population, innovative preventive measures should be developed and applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
125
5
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 37 publications
7
125
5
8
Order By: Relevance
“…Overall in-hospital mortality in the study population was 6.9%, with a mortality rate in patients with VAP of 45.7% vs 2.8% in patients without VAP (P ≤ .001). However, in a recent European multicenter study [40], a VAP incidence rate of 2.2%, lower than that found in our and other studies [3,38,39], was identified.…”
Section: Discussioncontrasting
confidence: 90%
“…Overall in-hospital mortality in the study population was 6.9%, with a mortality rate in patients with VAP of 45.7% vs 2.8% in patients without VAP (P ≤ .001). However, in a recent European multicenter study [40], a VAP incidence rate of 2.2%, lower than that found in our and other studies [3,38,39], was identified.…”
Section: Discussioncontrasting
confidence: 90%
“…This study did not analyze the impact of such variables on the mortality rate of VAP simply because it was not the aim of this work. However, the study data referring to the average time before VAP commences (5.5 days), appropriate antibiotic therapy (64%), presence of bacteremia (44.8%), and the distribution of common isolated pathogens in cultures are in accordance with those found in other studies [3,16,18,23,38,39].…”
Section: Discussionsupporting
confidence: 88%
“…Death was significantly more frequent in patients with VAP (57.1%) than in any other group. In a study of 1844 patients, Hortal et al [39] found that the cumulative incidence of VAP during the study period was 5.7%. Overall in-hospital mortality in the study population was 6.9%, with a mortality rate in patients with VAP of 45.7% vs 2.8% in patients without VAP (P ≤ .001).…”
Section: Discussionmentioning
confidence: 97%
“…1,4 It is therefore essential to further efforts to prevent VAP and to identify predisposing risk factors to control them. 5 The patient's own flora is a primary source of microorganisms for the development of this pathology. Aspiration of microorganisms from the aerodigestive tract has been involved in the physiopathology of VAP and is the most important risk factor for colonization of the oropharynx.…”
Section: Introductionmentioning
confidence: 99%